Atrophic Pigmented Dermatofibrosarcoma Protuberans: A Case Report and Literature Review - Bai, Juan; Liu, Bin; Liu, Taoming; Qiao, Jianjun; Fang, Hong (Frontiers in Oncology, 2021)
Dermatofibrosarcoma protuberans (DFSP) is a rare soft tissue sarcoma characterized by spindle cell proliferation in a storiform arrangement. We report a case of DFSP presented with bluish-black atrophic plaque. The tumor manifested as the characteristic of both pigmented and atrophic variant DFSP in histopathology. In the present report, we also reviewed previous published cases. Identification the clinical and histological characteristic of this DFSP variant can promote clinicians to manage patients with the DFSP at early stage.